Employee Well-being as a Mediator between Financial Compensation and Organizational Performance - Rolia Wahasusmia (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2026)
This study examines the role of employee well-being as a mediating variable in the relationship between financial compensation and organizational performance. The background of this research is the phenomenon that an increase in financial compensation is not always associated with optimal improvements in employee performance. This study uses a quantitative, explanatory research design and involves employees from various sectors as respondents. Data were collected using a Likert-scale questionnaire and analyzed using the SEM-PLS method to test the direct and indirect relationships among variables. The results of the study show that financial compensation has a positive and significant effect on employee well-being, and employee well-being has a significant effect on organizational performance. Meanwhile, the direct effect of compensation on organizational performance is relatively weaker than the indirect influence through well-being. This indicates that employee well-being plays a strong mediating role. Overall, this study confirms that organizational performance is influenced not only by financial factors but also by employee well-being. These findings provide important implications for organizations to integrate compensation policies with employee well-being improvement strategies.